Judicial Application of the Anti-Domestic Violence Law in Rural Courts: A Case Study of Henan and Sichuan Provinces (2016–2023) - Yanan Liu; Minghui Zhao (Studies in Law and Justice, 2025)
This paper investigates the judicial application of China’s Anti-Domestic Violence Law (2015) in rural courts, focusing on selected counties in Henan and Sichuan provinces between 2016 and 2023. Drawing on court documents, policy reports, and NGO data, it explores how local courts interpret and enforce protection orders, navigate evidentiary standards, and reflect embedded cultural norms. Despite the law’s rights-based framework and procedural tools, enforcement in rural areas remains inconsistent, shaped by infrastructural limitations, mediation culture, and judicial discretion. The study reveals that formal legal protection is frequently overridden by informal norms, narrow interpretations of harm, and resource scarcity. The paper calls for a more contextually grounded and gender-sensitive enforcement model that strengthens procedural accountability while reshaping rural legal consciousness.